Comparing the efficiency of vacuum ultraviolet and ultraviolet-C for the degradation of Remdesivir in the contaminated water - Mahboobeh Motalebi; Gholamreza Moussavi; Sakine Shekoohiyan (سلامت و محیط, 2023)
Background and Objective: Vacuum Ultraviolet (VUV)-based advanced oxidation is a new category of advanced purification processes, so this study aimed to compare the efficiency of VUV and Ultraviolet-C (UVC) processes in combination with H2O2 and PMS in degrading Remdesivir. Materials and Methods: The photoreactor was investigated with VUV and UVC lamps in combination with H2O2 and PMS for Remdesivir degradation. Also, the effect of variables such as solution pH, H2O2 dose, Remdesivir concentration, the presence of radical scavengers and anions, as well as hydraulic retention time was considered in the continuous process of Remdesivir removal. Results: The findings showed that the optimal pH in the processes of VUV, UVC, and their derivatives was equal to 7. By adding 1 mM of PMS and H2O2 to the VUV process, the degradation efficiency of Remdesivir was increased from 92.2 ± 0.4% to 98.3 ±2.1% and 100 ± 0.3%, respectively, after 30 min. Also, in the UVC process combined with H2O2 and PMS, the degradation efficiency reached 77.8 ± 1.5 and 85.2 ± 1.3% after 40 min, respectively. The degradation kinetics in the examined processes were as follows: VUV/H2O2 > VUV/PMS > VUV > UVC/H2O2 > UVC/PMS > UVC. The hydroxyl radical was the main reactive oxygen species that led to the decomposition of Remdesivir. The continuous operation of VUV/H2O2 showed that the removal efficiency of Remdesivir reached 94.7 ±0.8% after 40 min. Conclusion: Considering the high rate of Remdesivir degradation by adding H2O2, the VUV/H2O2 process can be introduced as an efficient technology for the removal of antiviral drugs.